Urgency of stimulating interest in purchase of digital-based services influenced by brand awareness, promotion, and customer satisfaction (Study on Gojek) - Mahmud, Muhamad Farid; Marchus, Patricia Alprits (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
The interest of GoJek customers is the ultimate goal in maintaining and expanding customer loyalty. The agility of digital-based services such as GoJek plays a crucial role in meeting mobility and solutions in various cities in Indonesia when facing congestion. In the digital era, online transportation services are growing rapidly, challenging competition by strengthening brands, promotions, and excellent service quality. This study endeavor to examine and scrutinize the influence of brand awareness, promotions and customer satisfaction in stimulating interest in using GoJek services at the Faculty of Economics, Gunadarma University. Employing quantitative methods to analyze the relationship between exogenous and endogenous constructs, based on primary data obtained from 157 respondents. Data analysis uses the Structural Equation Model approach or path analysis, with the SmartPls 4 application, making it possible to map the priority scale of each latent variable construct indicator. The results of this study reveal that brand awareness plays an important role in stimulating purchase interest, especially the dimensions of brand purchase and consumption, but promotions and customer satisfaction also strengthen the interest of GoJek customers to subscribe. Minat pengguna jasa GoJek menjadi tujuan akhir dalam menjaga dan memperluas loyalitas pelanggan. Kelincahan layanan berbasis digital seperti GoJek memegang peranan krusial dalam memenuhi mobilitas dan solusi di berbagai kota di Indonesia saat menghadapi kemacetan. Di era digital, layanan transportasi daring tumbuh pesat, menantang persaingan dengan memperkuat merek, promosi, dan kualitas layanan yang prima. Penelitian ini berupaya untuk mengkaji dan menguji pengaruh brand awareness, promosi dan kepuasan pelanggan dalam menstimulasi minat penggunaan layanan GoJek di Fakultas Ekonomi Universitas Gunadarma. Menggunakan metode kuantitatif untuk menganalisis hubungan antara konstruk eksogen dan endogen, berdasarkan data primer yang diperoleh dari 157 responden. Analisis data menggunakan pendekatan Structural Equation Model atau analisis jalur, dengan aplikasi SmartPls 4, sehingga memungkinkan untuk memetakan skala prioritas setiap indikator konstruk variabel laten. Hasil penelitian ini mengungkap bahwa brand awareness memegang peranan penting dalam menstimulasi minat pembelian, terutama dimensi pembelian dan konsumsi merek, namun promosi dan kepuasan pelanggan juga turut memperkuat minat pengguna jasa GoJek untuk berlangganan.